Teeth restoration for overdenture support - Brković Snežana; Poštić Srđan; Ilić Dragan (Serbian Medical Society - Dental Section, Belgrade, 2011)
Introduction. If patients have remained only a few teeth in one jaw, these teeth can be retained and specifically prepared to bear mobile supradental prosthesis i.e. overdenture (OD). The patients are usually very motivated to preserve remained teeth. The aim of this study was to present the plan, the preparation procedure and the treatment protocol for the remaining teeth that will bear full mobile OD. Material and Methods. Study included 12 patients and 23 remaining teeth. Treatment plan considered: radiological analysis and selection of the remaining teeth, reduction of the clinical crown of the teeth, endodontic and periodontal treatment and finally conservative or prosthodontic restoration of these teeth. Fifteen teeth were restored using cast crown build-up (cap) and eight teeth were restored with amalgam restorations. Patients who received twelve lower mobile full OD were observed for one year to assess the integrity of the extra alveolar tooth structure. Results. After observation period of one year, the integrity of crown restorations was maintained as well as the alveolar bone height. Conclusion. The restoration of the remaining teeth using cast crown build-up (cap) and amalgam is very important for maintaining extra alveolar tooth structure and successful treatment with overdentures.